Perlindungan Hukum terhadap Pasien Atas Tindakan Medis yang tidak disertai Informed Consent - Sistini Sistini (Majelis: Jurnal Hukum Indonesia, 2024)
Informed Consent is the patients content to medical action after the patient has received a complete explanation of the medical action to be performed. The purpose of informed consent, among others is to grants autonomy to the patient, as protection and prevent the occurrence of fraud / coercion agains all medical actions carried out without the patient knowledge. Before do medical action doctor must get approval. Doctor and patient tied together in a relationship named therapeutic agreement or therapeutic transaction. The doctor is not promising recovery but effortless for patient recovery. Medical action which is not accompanied informed consent risk of conflict. The hospital also shall be responsible if a lawsuit has occurred.